2021
DOI: 10.5415/apallergy.2021.11.e16
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of pollen season and coronavirus disease 2019 pandemic: less time outdoors - lesser allergy symptoms in 2020

Abstract: Background This year, pollen season coincided with the first wave of the coronavirus disease 2019 pandemic. Strict preventive measures have been implemented during April and May and then a normalization phase started in our country in June. Our aim is to evaluate the effect of preventive measures during the pandemic process on allergic airway disease symptoms. Methods A prospective questionnaire-based study was planned and a questionnaire form was sent to the cell-phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…26 There had also been a report of decreased AR disease burden in relation to altered behaviours during the pandemic (e.g., working from home, spending less time outdoors) -Sözener et al found that AR patients spent less time outdoors during the 2020 pollen season reported a reduction in AR symptoms. 27 An ancillary finding within the case-control HMR was that increasing age was found to be associated with decreased anxiety after controlling for the effect of the other predictor variables -β=-.17, p<.001 and β=-.18, p<.001 in Model 1a and in Model 1b, respectively (Table 2). This finding contradicts the thought that higher anxiety would be seen with increasing age since older people are at greater risk of serious illness following COVID-19 infection -a systematic review with meta-analysis of 70 pandemic-time studies found a continuous increase in COVID-19 disease severity with increasing age.…”
Section: Summary Of Results and Comparison To Existing Literaturementioning
confidence: 90%
“…26 There had also been a report of decreased AR disease burden in relation to altered behaviours during the pandemic (e.g., working from home, spending less time outdoors) -Sözener et al found that AR patients spent less time outdoors during the 2020 pollen season reported a reduction in AR symptoms. 27 An ancillary finding within the case-control HMR was that increasing age was found to be associated with decreased anxiety after controlling for the effect of the other predictor variables -β=-.17, p<.001 and β=-.18, p<.001 in Model 1a and in Model 1b, respectively (Table 2). This finding contradicts the thought that higher anxiety would be seen with increasing age since older people are at greater risk of serious illness following COVID-19 infection -a systematic review with meta-analysis of 70 pandemic-time studies found a continuous increase in COVID-19 disease severity with increasing age.…”
Section: Summary Of Results and Comparison To Existing Literaturementioning
confidence: 90%
“…A previous study performed in Spain showed that high pollen levels caused an increase in hospitalizations due to asthma [ 26 ]. A prospective questionnaire-based study in Turkey reported that exposure to pollen and allergic symptoms could be reduced in patients with pollen allergies by reducing outdoor activity during the pollen season and wearing a mask [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that those sensitized to outdoor allergens benefit from face mask usage. [17][18][19]22,24,25,27 In contrast, those sensitized to indoor allergens showed indifference when wearing a face mask and worsening symptoms during lockdown. 2,18,19,25 More than 45% of respondents agreed/ strongly agreed that the type of face mask available in the market has a role in giving them the desired reduction of symptoms.…”
Section: Attitude Domainmentioning
confidence: 98%
“…Previous studies have shown that during the COVID-19 global pandemic, there has been a decrease in allergic rhinitis symptoms among patients 2,6,[17][18][19][20][21][22][23][24][25][26][27][28][29] This can be attributed to two possible reasons: first, the reduced exposure to allergens because of the COVID-19 lockdown and avoidance of crowded places. Second, the use of face masks as per COVID-19 safety guidelines.…”
Section: Symptoms Of Allergic Rhinitis Domainmentioning
confidence: 99%